DAMPAK DANA DESA TERHADAP PEMBANGUNAN DESA DAN PEMBERDAYAAN MASYARAKAT DESA (STUDI KASUS PADA DESA CIBITUNG KECAMATAN SAGARANTEN KABUPATEN SUKABUMI) - Deri Firmansyah; Dwinanto Priyo Susetyo; Mira Sumira (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
The priority of village funds is used to finance the implementation of village programs and activities in the field of village development and village community empowerment. The development and empowerment of village communities can be carried out well if the management of village funds is carried out in a transparent, accountable, orderly and disciplined budget as well as the participation of various parties. The purpose of this study was to determine the effect of village funds on village development and village community empowerment (Case Study in Cibitung Village, Sagaranten District, Sukabumi). The research method used in this research is the mix method. The object of this research is the people of Cibitung Village, Sagaranten Sukabumi District, the sampling technique in this study was determined by quota sampling of 110 respondents. For statistical analysis simple linear regression analysis is used, the coefficient of determination and to test the hypothesis the t test is used. Based on the results of research and data analysis that has been done, the test results are obtained that the management and distribution of village funds on target can have an impact on the progress of village development and empowerment of rural communities so as to encourage the development of community independence and increase the welfare of village communities.